Primary healthcare costs associated with sleep problems up to age 7 years: Australian population-based study. Issue 5 (30th May 2013) - Quach, J; Gold, L; Hiscock, H; Mensah, F K; Lucas, N; Nicholson, J M; Wake, M
Abstract : Objectives: In Australian 0–7-year olds with and without sleep problems, to compare (1) type and costs to government of non-hospital healthcare services and prescription medication in each year of age and (2) the cumulative costs according to persistence of the sleep problem. Design: Cross-sectional and longitudinal data from a longitudinal population study. Setting: Data from two cohorts participating in the first two waves of the nationally representative Longitudinal Study of Australian Children. Participants: Baby cohort at ages 0–1 and 2–3 (n=5107, 4606) and Kindergarten cohort at ages 4–5 and 6–7 (n=4983, 4460). Measurements: Federal Government expenditure on healthcare attendances and prescription medication from birth to 8 years, calculated via linkage to Australian Medicare data, were compared according to parent report of child sleep problems at each of the surveys. Results: At both waves and in both cohorts, over 92% of children had both sleep and Medicare data. The average additional healthcare costs for children with sleep problems ranged from $141 (age 5) to $43 (age 7), falling to $98 (age 5) to $18 (age 7) per child per annum once family socioeconomic position, child gender, global health and special healthcare needs were taken into account. This equates to an estimated additional $27.5 million (95% CI $9.2 to $46.8 million) cost to the Australian federal government every year for all children aged between 0 and 7 years. In both cohorts, costs were higher for persistent than transient sleep problems. Conclusions: Higher healthcare costs were sustained by infants and children with sleep problems. This supports ongoing economic evaluations of early prevention and intervention services for sleep problems considering impacts not only on the child and family but also on the healthcare system.